Endothelin Inhibition Potentiates Cancer Immunotherapy Revealing Mechanical Biomarkers Predictive of Response (Adv. Therap. 9/2021). Issue 9 (21st September 2021) - Voutouri, Chrysovalantis; Panagi, Myrofora; Mpekris, Fotios; Stylianou, Andreas; Michael, Christina; Averkiou, Michalakis A.; Martin, John D.; Stylianopoulos, Triantafyllos
Abstract : Bosentan, an endothelin‐receptor blocker, can both normalize the tumor microenvironment, reprograming fibroblasts and reducing collagen thereby decompressing tumor blood vessels, and also increase T cell adhesion to the tumor vasculature. Together these effects significantly improve the efficacy of immune checkpoint inhibition. In addition, mechanical biomarkers derived from ultrasound elastography can predict the tumor response to immunotherapy. This is reported by John D. Martin, Triantafyllos Stylianopoulos, and co‐workers in article number 2000289 .